The various and shared roles of lncRNAs during development. Issue 11 (13th September 2019) - Murillo‐Maldonado, Juan M.; Riesgo‐Escovar, Juan R.
Abstract: lncRNAs, genes transcribed but not translated, longer than 200 nucleotides, are classified as a separate class of nonprotein coding genes. Since their discovery, largely from RNAseq data, a number of pioneer studies have begun to unravel its myriad functions, centered on gene expression regulation, suggesting developmental and evolutionary conservation. Since they do not code for proteins and have no open reading frames, their functional constraints likely differ from that of protein coding genes, or of genes where the majority of the nucleotide sequence is required for function, like tRNAs. This has complicated assessment of both developmental and evolutionary conservation, and the identification of homologs in different species. Here we argue that other characteristics: general synteny and particular chromosomal placement regardless of sequence, sequence micro‐motifs, and secondary structure allow for "homologs" to be identified and compared, confirming developmental and evolutionary conservation of lncRNAs. We conclude exemplifying a case in point: that of the evolutionarily conserved lncRNA acal, characterized and required for embryogenesis in Drosophila. Key Findings: lncRNAs are a heterogeneous class of RNA genes. Homology in lncRNAs relies on several points: synteny, micro‐domains, and secundary structure. Common function may imply common evolutionary origin.